The Effect Of Triple Dip La Niña On Rainfall In Lombok During 2020–2023 - Rohman, Muhammad Faisal; Sabrina, Purwanti Lelly; Avrionesti, Avrionesti (Program Pascasarjana Universitas Sriwijaya, 2025)
Triple Dip La Niña is a term that describes the La Niña phenomenon that lasts for 3 consecutive years. History records that this phenomenon last occurred in 1973–1976 and 1998–2001 which influenced the regional weather system through the mechanism of atmosphere-ocean interaction, one of which was in Lombok. This study was conducted to analyze the impact of the emergence of the Triple Dip La Niña phenomenon on rainfall variability in Lombok from 2020 to 2023, as well as to test the correlation of the ENSO relationship indicated by the ONI (Oceanic Niño Index) indicator with rainfall variables. The data used in this study were monthly rainfall data from 55 rain posts and ONI data from NOAA. The results showed that the influence of Triple Dip La Niña on rainfall variability was observed most significantly in the dry season (JJA) with an increase in rainfall >100%. A strong relationship between the ONI index and rainfall was identified in Senaru, Bayan, Janapria, and Pringgabaya.